2021
DOI: 10.1177/1356336x211046300
|View full text |Cite
|
Sign up to set email alerts
|

Video modeling examples are effective tools for self-regulated learning in physical education: Students learn through repeated viewing, self-talk, and mental rehearsal

Abstract: This study aimed at assessing the impact of video modeling examples (VMEs) on secondary school students’ self-regulated learning experiences in gymnastics in original physical education (PE) settings. A total of 56 students (28 males and 28 females), aged 16–17, took part in a seven-week gymnastics learning unit for the purpose of acquiring new motor skills and knowledge using VMEs, in the absence of teacher and peer assistance. Repeated measurements were collected through gymnastics floor routines and a custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…The results recorded in the present study confirm those reported in several previous studies that confirmed that incorporating VM was a good strategy to induce beneficial improvements in terms of specific skills in both individuals (e.g., gymnastics, weightlifting) [ 15 , 16 , 53 ], and team sports such as soccer and basketball [ 54 , 55 , 56 ]. Specifically, in basketball, passing skills were found to be higher in VMG compared to CG.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results recorded in the present study confirm those reported in several previous studies that confirmed that incorporating VM was a good strategy to induce beneficial improvements in terms of specific skills in both individuals (e.g., gymnastics, weightlifting) [ 15 , 16 , 53 ], and team sports such as soccer and basketball [ 54 , 55 , 56 ]. Specifically, in basketball, passing skills were found to be higher in VMG compared to CG.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it has been revealed that most of the information that reaches the brain is acquired through the eyes/visualization [ 12 , 13 ]. From this perspective, various studies have suggested that VM is an effective strategy that induces learning improvements and enhances athletic movements such as gymnastics skills [ 9 , 14 , 15 ], snatch movement in weightlifting [ 16 ], tennis service [ 17 ], basketball shooting form [ 18 , 19 , 20 ], and basketball tactical skills [ 20 , 21 , 22 , 23 ]. This is particularly true, as digital environments allow coaches to use videos to analyze athletic movements, evaluate their team performance, and adjust their collective strategies and individual technical skills to enhance their performance [ 5 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Is There a Clear Statement of Findings? [ 47 ] 1 1 1 1 1 0 1 1 1 [ 48 ] 1 1 1 1 1 0 1 1 1 [ 30 ] 1 ? 1 1 1 0 1 1 1 [ 14 ] 1 1 1 1 1 1 1 1 1 [ 49 ] 1 1 1 1 1 0 1 1 ?…”
Section: Resultsmentioning
confidence: 99%
“…Most of the data focus on performance in three aspects during learning processes: 6 articles (30%) focus on metacognitive processes,12 articles (60%) focus on self-regulation, and two articles (10%) focus on executive functions. The sports disciplines include soccer, 30 , 47 , 62 gymnastics, 48 endurance running, 14 , 51 , 55 golf, 49 taekwondo, 50 , 60 MMA, 54 , 56 , 61 yoga, 52 table tennis, 57 hockey, 63 and metacognition-related physical education programs. 53 , 58 , 59 , 64 Most studies indicate that metacognitive performance varies across different sports disciplines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation